Functional characterization of a flavonoid glycosyltransferase gene from withania somnifera (Ashwagandha) - Singh, Somesh; Vishwakarma, Rishi. K.; Kumar, R. J. Santosh; Sonawane, Prashant D.; Ruby; Khan, Bashir Mohammad (Applied Biochemistry and Biotechnology, 2013)
Glycosylation of flavonoids is mediated by family 1 uridine diphosphate (UDP)-dependent glycosyltransferases (UGTs). Until date, there are few reports on functionally characterized flavonoid glycosyltransferases from Withania somnifera. In this study, we cloned the glycosyltransferase gene from W. somnifera (UGT73A16) showing 85-92 % homology with UGTs from other plants. UGT73A16 was expressed as a His(6)-tagged fusion protein in Escherichia coli. Several compounds, including flavonoids, were screened as potential substrates for UGT73A16. HPLC analysis and hypsochromic shift indicated that UGT73A16 transfers a glucose molecule to several different flavonoids. Based on kinetic parameters, UGT73A16 shows more catalytic efficiency towards naringenin. Here, we explored UGT73A16 of W. somnifera as whole cell catalyst in E. coli. We used flavonoids (genistein, apigenin, kaempferol, naringenin, biochanin A, and daidzein) as substrates for this study. More than 95 % of the glucoside products were released into the medium, facilitating their isolation. Glycosylation of substrates occurred on the 7- and 3-hydroxyl group of the aglycone. UGT73A16 also displayed regiospecific glucosyl transfer activity towards 3-hydroxy flavone compound, which is the backbone of all flavonols and also for a chemically synthesized compound, not found naturally. The present study generates essential knowledge and molecular as well as biochemical tools that allow the verification of UGT73A16 in glycosylation.
Keywords: Flavonoid; glycosylation; Glycosyltransferase; Hypsochromic shift; Plant secondary product glycosyltransferase (PSPG); Withania somnifera

Functional characterization of a glucosyltransferase specific to flavonoid 7-O-glucosides from withania somnifera - Kumar, R. J. Santosh; Ruby; Singh, Somesh; Sonawane, Prashant D.; Vishwakarma, R. K.; Khan, Bashir Mohammad (Plant Molecular Biology Reporter, 2013)
Flavonoids are a large class of phenylpropanoid-derived secondary metabolites, which are usually glycosylated by UDP-glycosyltransferases with one or more sugar groups. Here, we report the cloning and biochemical characterization of a flavonoid glycosyltransferase gene from Withania somnifera (WsGT), which is an important medicinal plant used in Ayurvedic formulations. Using PCR primers, designed for a highly conserved region of previously reported glycosyltransferases, we were able to isolate the corresponding fragment of the WsGT gene. Rapid amplification of cDNA ends (RACE) was then employed to isolate full-length cDNA, which had an open reading frame of 1,371 bp that encode for 456 amino acids. Phylogenetic analysis indicated that WsGT was similar to that of family 1 GT-B glycosyltransferase. Biochemical analysis revealed that WsGT interacts with UDP-glucose and was capable of regiospecifically glycosylating flavonoid-7-ols, such as apigenin, naringenin, luteolin, diadzein and genistein. Expression profiling studies showed that WsGT was highly expressed in young and mature leaves of W. somnifera. Furthermore, exposure to salicylic acid enhanced the expression of WsGT in the leaves and heat shock treatment resulted in decreased expression of WsGT after an initial increase. This may suggest the role of WsGT in response to abiotic/biotic stresses.
Keywords: Diadzein; Flavonoids; Glycosyltransferase; Withania somnifera

Molecular cloning and characterization of genistein 4'-O-glucoside specific glycosyltransferase from Bacopa monniera - Ruby; Kumar, R. J. Santosh; Vishwakarma, Rishi K.; Singh, Somesh; Khan, Bashir Mohammad (Molecular Biology Reports, 2014)
Health related benefits of isoflavones such as genistein are well known. Glycosylation of genistein yields different glycosides like genistein 7-O-glycoside (genistin) and genistein 4'-O-glycoside (sophoricoside). This is the first report on isolation, cloning and functional characterization of a glycosyltransferase specific for genistein 4'-O-glucoside from Bacopa monniera, an important Indian medicinal herb. The glycosyltransferase from B. monniera (UGT74W1) showed 49 % identity at amino acid level with the glycosyltransferases from Lycium barbarum. The UGT74W1 sequence contained all the conserved motifs present in plant glycosyltransferases. UGT74W1 was cloned in pET-30b (+) expression vector and transformed into E. coli. The molecular mass of over expressed protein was found to be around 52 kDa. Functional characterization of the enzyme was performed using different substrates. Product analysis was done using LC-MS and HPLC, which confirmed its specificity for genistein 4'-O-glucoside. Immuno-localization studies of the UGT74W1 showed its localization in the vascular bundle. Spatio-temporal expression studies under normal and stressed conditions were also performed. The control B. monniera plant showed maximum expression of UGT74W1 in leaves followed by roots and stem. Salicylic acid treatment causes almost tenfold increase in UGT74W1 expression in roots, while leaves and stem showed decrease in expression. Since salicylic acid is generated at the time of injury or wound caused by pathogens, this increase in UGT74W1 expression under salicylic acid stress might point towards its role in defense mechanism.
Keywords: Bacopa monniera; Expression analysis; Glycosyltransferase; Immuno-localization; Plant secondary product glycosyltransferase motif

Semirational design and engineering of grapevine glucosyltransferases for enhanced activity and modified product selectivity - Joshi, Rakesh; Trinkl, Johanna; Haugeneder, Annika; Haertl, Katja; Franz-Oberdorf, Katrin; Giri, Ashok; Hoffmann, Thomas; Schwab, Wilfried (Glycobiology, 2019)
Uridine diphosphate-dependent glycosyltransferases (UGTs) catalyze the transfer of a diversity of sugars to several acceptor molecules and often exhibit distinct substrate specificity. Modulation of glycosyltransferases for increased catalytic activity and altered substrate or product specificity are the key manipulations for the biotechnological use of glycosyltransferases in various biosynthetic processes. Here, we have engineered the binding pocket of three previously characterized Vitis vinifera glycosyltransferases, UGT88F12, UGT72B27 and UGT92G6, by structure-guided in silico mutagenesis to facilitate the interactions of active site residues with flavonol glucosides and thus modify substrate specificity and activity. Site-directed mutagenesis at selected sites, followed with liquid chromatography-mass spectrometry based activity assays, exhibited that mutant UGTs were altered in product selectivity and activity as compared to the wild-type enzymes. Mutant UGTs produced larger amounts of flavonol di-monosaccharide glucosides, which imply that the mutations led to structural changes that increased the volume of the binding pocket to accommodate a larger substrate and to release larger products at ease. Mutants showed increased activity and modified product specificity. Thus, structure-based systematic mutations of the amino acid residues in the binding pocket can be explored for the generation of engineered UGTs for diverse biotechnological applications.
Keywords: flavonol; Glycosyltransferase; in silico analysis; Mutagenesis; selectivity

Aroma Alchemy: uridine diphosphate-dependent glycosyltransferases mediated regulation of fruit aroma and flavor biosynthesis - Vare, Tejas B.; Joshi, Rakesh S.; Giri, Ashok P. (Phytochemistry Reviews, 2024)
The aroma compounds contribute to fruits flavor, taste, and nutritional value. These compounds include various chemical classes such as terpenoids, lactones, ketones, esters, acids, alcohols, and their derivatives. Uridine diphosphate-dependent glycosyltransferases (UGTs) modify these compounds by covalently adding one or multiple sugar molecules. This glycosylation process converts volatile, unstable, and hydrophobic aroma compounds into hydrophilic, stable, and slow-releasing reservoirs of fruit flavor. The diversity and spatio-temporal expression patterns of UGTs play a crucial role in forming a wide range of glycosylated aroma compounds. This review focuses on aroma-related compounds in both free and glycosylated-bound forms found in commercial vital fruits. We discuss various fruit-specific UGTs and their role in the glycosylation of aroma compounds. Based on structural and functional information on UGTs, we have assessed sugar donor specificity and the residues responsible for the same. Moreover, phylogenetic analysis of characterized UGTs provides insights into their substrate preferences. We also surveyed the expression dynamics of UGTs during fruit ripening, as the switching between aglycon and glycosylated-bound forms of aroma compounds significantly impacts fruit quality. Potential applications of UGTs in the food and fragrance industry have been discussed. The information reviewed could be beneficial for developing novel methods for flavor manipulation of commercially important glycosides derived from natural resources.
Keywords: Aroma; Flavor; Fruit; Glycoconjugates; Glycosyltransferase; Volatile compounds